Os desafios para a saúde - Carvalheiro, José R. (Estudos Avançados, 1999)
THIS PAPER emphasizes the economic nature of health care at a time when the tertiary sector is the one fastest growing in economy and health care is the most dynamic. It touches upon the public health crisis considering health problems, methods and services. The epistemic community concept is used to analyse the current situation. Two trends are identified, exhibiting distinct conceptual paradigms: one in Public Health, the other in Health Economics. The main agencies for the formulation of those paradigms are, respectively, the World Health Organization and the World Bank. On the national level, the 1988 Constitution provided a universal Unified Health System (SUS - Sistema Unificado de Saúde), complete in its activities, decentralized and fully engaged, under social control. The SUS has been established according to the Operational Rules and the compensation mechanisms represented by its Intermanaging Committees. An issue not yet fully settled is the SUS finacing.